Implementation Natural and Social Sciences with a Language-Based Differentiated Approach to Improve Elementary School Student Learning Outcomes - Midya Botty; Amir Hamzah; Ade Taufan; Nelly Patria; Thoriq; Amanda Maharani (MIMBAR PGSD Undiksha, 2025)
The lack of learning approaches that can accommodate students' individual needs, especially in terms of learning styles, interests, and language abilities, presents a challenge in improving the quality of education at the elementary school level. This study aims to analyze the implementation of IPAS (Science, Social Studies, and Arts) learning with a language based differentiated approach and explore its impact on the learning process and student achievement. The research uses a qualitative approach with a multisite study design, involving teachers and students as research subjects. Data were collected through observations, interviews, documentation, and formative assessments, with a focus on understanding students' needs. Data analysis was carried out through the stages of reduction, presentation, and interactive conclusion drawing. The implementation of this strategy enhanced students’ motivation, active participation, communication skills, and learning outcomes. Its success was supported by teachers’ competence and creativity, parental involvement, and adequate facilities. Challenges included limited preparation time, complex classroom management, and insufficient resources. Overall, IPAS learning with a differentiated language approach proved effective in improving learning quality, highlighting the need to strengthen teachers’ pedagogical capacity and provide better learning facilities.